2011
DOI: 10.1108/10444061111103643
|View full text |Cite
|
Sign up to set email alerts
|

Women inSulha– excluded yet influential

Abstract: Purpose -This paper aims to locate, describe and analyze the mechanism and impact of women's informal role within the formally male-only Sulha -a prevalent, inter/intra-communal dispute resolution process practiced by Muslim, Christian and Druze Arabs in Israel and in many other regions of the Middle East and the Muslim world. Furthermore, this paper seeks to explore the way men's formal roles and women's informal roles interact within the Sulha's strict patriarchal settings. Design/methodology/approach -The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…With reference to the patriarchal society and the constraining socio-cultural traditions, Tlaiss (2015b) found that Emirati women entrepreneurs are motivated by the need for independence, a sense of accomplishment and control over their lives, reflecting the achievement of these women in challenging their socio-cultural expectations. Pely (2010) found that even in a highly patriarchal setting such as the "Sulha" process, women tend to play a very significant informal role at each stage and their involvement is acknowledged by both genders. "Sulha" is a common process of conflict resolution adopted by Arabs (Muslims, Christians and Druze) (Pely, 2010).…”
Section: Enhancing Women's Leadershipmentioning
confidence: 99%
See 2 more Smart Citations
“…With reference to the patriarchal society and the constraining socio-cultural traditions, Tlaiss (2015b) found that Emirati women entrepreneurs are motivated by the need for independence, a sense of accomplishment and control over their lives, reflecting the achievement of these women in challenging their socio-cultural expectations. Pely (2010) found that even in a highly patriarchal setting such as the "Sulha" process, women tend to play a very significant informal role at each stage and their involvement is acknowledged by both genders. "Sulha" is a common process of conflict resolution adopted by Arabs (Muslims, Christians and Druze) (Pely, 2010).…”
Section: Enhancing Women's Leadershipmentioning
confidence: 99%
“…Pely (2010) found that even in a highly patriarchal setting such as the "Sulha" process, women tend to play a very significant informal role at each stage and their involvement is acknowledged by both genders. "Sulha" is a common process of conflict resolution adopted by Arabs (Muslims, Christians and Druze) (Pely, 2010). A study of Western women living in the Arab world, the ethnographic investigation of Lauring and Selmer (2010), found that Danish spouses of male expatriates in Saudi Arabia who were not allowed to do paid work took on new gender roles.…”
Section: Enhancing Women's Leadershipmentioning
confidence: 99%
See 1 more Smart Citation